2011
DOI: 10.3899/jrheum.101049
|View full text |Cite
|
Sign up to set email alerts
|

Differential Features Between Primary Ankylosing Spondylitis and Spondylitis Associated with Psoriasis and Inflammatory Bowel Disease

Abstract: Patients with primary AS had more severe axial involvement than those with spondylitis associated with psoriasis or IBD. Functional capacity, disease activity, and quality of life were comparable among the groups studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 14 publications
2
37
2
8
Order By: Relevance
“…Moreover, there are a number of difficulties in measuring disease activity in patients with axPsA. Several previous studies reported that clinical features of axPsA including inflammatory back pain and limitation of spinal ASDAS-CRP ankylosing spondylitis disease activity score C-reactive protein, ASDAS-ESR ankylosing spondylitis disease activity score erythrocyte sedimentation rate, VAS pain visual analog scale for pain, BASDAI bath ankylosing spondylitis disease activity index, BASFI bath ankylosing spondylitis functional index, ESR erythrocyte sedimentation rate, CRP C-reactive protein, ASQoL ankylosing spondylitis quality of life questionnaire ASDAS-CRP ankylosing spondylitis disease activity score C-reactive protein, ASDAS-ESR ankylosing spondylitis disease activity score erythrocyte sedimentation rate, VAS pain visual analog scale for pain, BASDAI bath ankylosing spondylitis disease activity index, BASFI bath ankylosing spondylitis functional index, ESR erythrocyte sedimentation rate; CRP C-reactive protein, ASQoL ankylosing spondylitis quality of life questionnaire mobility as well as radiologic features are usually less severe than AS [7,8]. Furthermore, many of the patients with axPsA may be asymptomatic or have subclinical axial symptoms despite their spinal involvement [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are a number of difficulties in measuring disease activity in patients with axPsA. Several previous studies reported that clinical features of axPsA including inflammatory back pain and limitation of spinal ASDAS-CRP ankylosing spondylitis disease activity score C-reactive protein, ASDAS-ESR ankylosing spondylitis disease activity score erythrocyte sedimentation rate, VAS pain visual analog scale for pain, BASDAI bath ankylosing spondylitis disease activity index, BASFI bath ankylosing spondylitis functional index, ESR erythrocyte sedimentation rate, CRP C-reactive protein, ASQoL ankylosing spondylitis quality of life questionnaire ASDAS-CRP ankylosing spondylitis disease activity score C-reactive protein, ASDAS-ESR ankylosing spondylitis disease activity score erythrocyte sedimentation rate, VAS pain visual analog scale for pain, BASDAI bath ankylosing spondylitis disease activity index, BASFI bath ankylosing spondylitis functional index, ESR erythrocyte sedimentation rate; CRP C-reactive protein, ASQoL ankylosing spondylitis quality of life questionnaire mobility as well as radiologic features are usually less severe than AS [7,8]. Furthermore, many of the patients with axPsA may be asymptomatic or have subclinical axial symptoms despite their spinal involvement [23].…”
Section: Discussionmentioning
confidence: 99%
“…but also the radiologic changes identified in axPsA are usually milder than ankylosing spondylitis (AS) [7,8]. Overlap of spinal manifestations with peripheral joint involvement is common in PsA.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a study aimed to describe differential characteristics of axial involvement in AS compared with that seen in PsA and inflammatory bowel disease (IBD) in a cohort of patients. The study, including 2,044 consecutive patients with SpA, showed that primary AS had more severe axial involvement than those with spondylitis associated with psoriasis or IBD, while functional capacity, disease activity and quality of life were comparable among the groups studied [14]. Moreover, to support the assumptions that an equivalency between axial PsA and AS may not hold up, previous studies showed that the Bath Ankylosing Spondylitis Disease Activity score (BASDAI) in PsA was significantly lower than AS, correlated poorly with external indicators of disease activity [15] and may be influenced by the peripheral involvement, showing again the difference between these two conditions [16].…”
Section: Introductionmentioning
confidence: 95%
“…Однако, как показы-вают исследования, по функциональным возможностям, индексам активности спондилита, а также по уровню ка-чества жизни пациенты с аксПсА сопоставимы с больны-ми АС [12].…”
Section: Discussionunclassified